Diary of a wimpy kid. Rodrick rules Rodrick rules - Jacobson, Nina.; Simpson, Brad, 1973-; Bowers, David; Sachs, Gabe.; Judah, Jeff.; Gordon, Zachary, 1998-; Bostick, Devon, 1991-; Harris, Rachael, 1968-; Capron, Robert, 1998-; Zahn, Steve, 1968-; Kinney, Jeff.; Twentieth Century-Fox Film Corporation; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2011)
Back in middle school after summer vacation, Greg Heffley and his older brother Rodrick must deal with their parents' misguided attempts to have them bond.
DVD release of the 2011 motion picture.
Based upon the second volume of the book series by Greg Kinney.
Special features: hilarious My Summer Vacation shorts ; My Magick Summer by Greg Heffley ; My Zoo-Wee Vacation! by Rowley Jefferson.
Music, Edward Shearmur ; film editor, Troy Takaki ; director of photography, Jack Green.
Zachary Gordon, Devon Bostick, Rachael Harris, Robert Capron, Steve Zahn.
MPAA rating: PG; for some mild rude humor and mischief.
Keywords: Middle schools -- Juvenile drama; Friendship -- Juvenile drama; Schools -- Juvenile drama; Diaries -- Juvenile drama; Middle schools -- Drama; Friendship -- Drama; Schools -- Drama; Diaries -- Drama; Middle schools -- Drama; Friendship -- Drama; Schools -- Drama; Diaries -- Drama; Escuelas -- Teatro juvenil; Amistad -- Teatro juvenil; Diarios n̕timos -- Teatro juvenil; Children's films; Fiction films; Film adaptations; Feature films; Comedy films; DVD-Video discs; Video recordings for the hearing impaired